Key success factors: Test of a general theory in the mature industrial‐product sector - Sa, Jorge Alberto Sousa de Vasconcellos e; Hambrick, Donald C. (Strategic Management Journal, 1989)
Abstract This study tests the suppositions that (1) industries differ in their key success factors, and (2) firms whose strengths match those factors will perform well. A typology of mature industrial‐product industries, classified according to their core technology and transaction complexity, allows very strong prediction of key success factors in differing contexts. The ratings of key success factors by expert panels in six industries were in extremely close agreement with the hypotheses. Another set of expert panels in the six industries provided additional data which strongly indicated that firm profitability depends on having strengths that match the industry'S particular key success factors.